Percepções do ser adulto frente ao processo de viver e envelhecer com deficiência física : um estudo fenomenológico - Oliva, Daniela Regina Sposito Dias (2012)
The aging with disability becomes a challenge to be faced by this social group front of bigger probability of summation of disability, existential aspects and their perceptions towards on this phenomenon. These aspects are also interests of physiotherapist, understanding that the corporeal, the physical body, psychological, social and cultural, and the meaning of the phenomenon disabled. The objective is known, describe and understand the perceptions of a group of adults individuals facing the living and aging with disabilities, of the phenomenological view. The collaborators are four adults between 36 and 54 years with physical disabilities acquired, while young and adults. This study is based in the Phenomenology of Perception by Maurice Merleau-Ponty, whose emphasis is based to experience body and the body awareness of the sensible world, and in the phenomenological method proposed by Giorgi. The resulting essences of the phenomenological view, about living and aging with physical disabilities are four: 1) Realizing of the triggering event of disability, 2) Restarting: the pitfalls of a life trajectory, 3) Living with a disability and 4) Thinking the future: tomorrow is the struggle today. By revealing the things of the world that feel they are in themselves, the employees live and perceive disability facing adversity, fighting battles and efforts and finding ways to uncover opportunities, while transposing the barriers. The perception of such experiments requires an attention of the whole society, of the physiotherapist, in order to know that beyond the body deviant there are the body existential, it requires review of concepts and attitudes considering the intentionality of the body